EFEKTIVITAS THE 5E LEARNING CYCLE MODEL DENGAN PENDEKATAN INKUIRI BERBASIS ICT (INFORMATION & COMMUNICATION TECHNOLOGY) DALAM PEMBELAJARAN CHASSIS OTOMOTIF - Nugroho, Cahyo Aji (Jurnal Nosel, 2013)
The  purpose  of  this  research  is  to  know  the  effectiveness  of  inquiry  5e  learning cycle  model  based  on  ICT  on  learning  outcomes  and  students?  activity  in  teaching automotive chassis in class XII SMK Pancasila in 2012/2013 academic year. Related to the objective of the research, the research used experimental method. The  research  design  used  is  Quasi-  Experimental  Design  with  Pretest-  Posttest  and Control Group. The total number of population is 120 students coming from four classes. The  sampling  of  the  research  is  cluster  random  sampling.  From  the  population,  two classes/  clusters  were  taken  randomly  as  the  sample  so  there  are  two  classes  in  this research, experimental and control groups. Experimental group used inquiry 5e learning cycle model based on ICT, Control group used lecture model based on ICT. Technique  of the data collection consist of test and obsrvation letter.The data are analyzed by using t-test formula (t-test for independent sample). In this case, data which are analyzed are pre-test and post-test scores of the two groups. The result of t-test in  post-test computation shows that t observation (t0) is 3.73. Value tt with degree of freedom 48 of t table (tt) = 2.00. In this case, to = 3.73 is higher than tt = 2.00 (to  >   tt).  From  the  result,  there  are  significant  difference  learning  outcomes  between using inquiry 5e learning cycle model based on ICT and by using lecture based on ICT. Observation  result  from  observer  concluded,  there  are  significant  difference  on  the students? activity of chassis automotive between the students? taught by using inquiry 5e learning cycle model based on ICT and those taught by using lecture based on ICT. The experimental group show that students? activity better than control group.Based on the research finding above, it can be concluded that Inquiry 5e Learning Cycle  Model  Based  on  ICT  is  effective  to  learning  outcomes  and  students?  activity  in teaching automotive chassis in class XII SMK Pancasila in 2012/2013 academic year.